Adult Patient Presenting Rare Brain Tumour-Gliosarcoma (Pulse, 2016)
Gliosarcoma is a rare primary malignancy of the central nervous system, classified by the World Health Organization as a high-grade glioma and a variant of glioblastoma multiforme. A 57-year-old gentleman presented with a history of left-sided weakness and loss of appetite. Brain MRI was suggestive of right frontal and thalamic mass lesion with contrast enhancement at the periphery. Open biopsy examination revealed a malignant brain tumour presenting a biphasic tissue pattern with gliomatous and mesenchymal components suggestive of gliosarcoma. Although the treatment of gliosarcomas is almost similar to glioblastomas (surgical resection and, depending on clinical status, radiotherapy and/or chemotherapy) the prognosis of gliosarcomas remains poorPulse Vol.8 January-December 2015 p.85-88